Coordinated dispersal and pre-isthmian assembly of the Central American ichthyofauna - Tagliacollo, Victor Alberto [UNESP]; Duke-Sylvester, Scott M.; Matamoros, Wilfredo A.; Chakrabarty, Prosanta; Albert, James S. (Oxford University Press (OUP), 2015)
We document patterns of coordinated dispersal over evolutionary time frames in heroine cichlids and poeciliine live-bearers, the two most species-rich clades of freshwater fishes in the Caribbean basin. Observed dispersal rate (DO) values were estimated from time-calibrated molecular phylogenies in Lagrange+, a modified version of the ML-based parametric biogeographic program Lagrange. DO is measured in units of 'wallaces' (wa) as the number of biogeographic range-expansion events per million years. DO estimates were generated on a dynamic paleogeographic landscape of five areas over three time intervals from Upper Cretaceous to Recent. Expected dispersal rate (DE) values were generated from alternative paleogeographic models, with dispersal rates proportional to target area and source-river discharge volume, and inversely proportional to paleogeographic distance. Correlations between DO and DE were used to assess the relative contributions of these three biogeographic parameters. DO estimates imply a persistent dispersal corridor across the Eastern (Antillean) margin of the Caribbean plate, under the influence of prevailing and perennial riverine discharge vectors such as the Proto-Orinoco-Amazon (POA) river. Ancestral area estimation places the earliest colonizations of the Greater Antilles and Central America (GACA) during the Paleocene-Eocene (c. 58-45 Ma), potentially during the existence of an incomplete Paleogene Arc (~59 Ma) or Lesser Antilles Arc (~45 Ma), but predating the GAARlandia land bridge (~34-33 Ma). Paleogeographic distance is the single best predictor of DO. The Western (Central American) plate margin did not serve as a dispersal corridor until the Late Neogene (12-0 Ma), and contributed relatively little to the formation of modern distributions.
Keywords: Caribbean plate; Central america; Cichlidae; Greater antilles; Historical biogeography; Parametric biogeography; Poeciliidae